Convenient friction structure method of self-floating photo-thermal interface evaporator for brackish water desalination
By combining polyacrylate-based compounds with nano-scale inorganic materials, a fluorine-free superhydrophobic gel polymer was constructed. A self-floating photothermal interface evaporation device was constructed using simple reciprocating friction technology, which solved the bitter salt water desalination in the existing technology The problems of high equipment costs and high energy consumption have achieved efficient and environmentally friendly downplay.
Patent Information
- Application Number
- CN202411358722.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-10
AI Technical Summary
The existing bitter brackish water desalination technology has problems such as high power consumption, high operating costs, high equipment costs, difficult equipment maintenance, and relying on high-cost and difficult-to-degrade long fluorine materials during the preparation process.
The polyacrylate-based compounds are combined with nano-scale inorganic materials, and the hyperbranched gel polymer is formed by Michael addition reaction at room temperature, and the long-chain alkyl amine is used for low surface energy modification, and the construction is constructed with simple reciprocating friction technology. Fluorine-free superhydrophobic gel polymer is used to construct self-floating photothermal interface evaporation devices.
It realizes the desalination of bitter salt water with low cost, low energy consumption and simple processes, reduces equipment maintenance costs, and improves evaporation efficiency through wetting asymmetric characteristics. The material is non-toxic and bioaccumulative, and meets the requirements of green and environmental protection.
Smart Images

Figure CN119286051A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of photothermal composite materials and water purification, and in particular to a convenient friction construction method for a self-floating photothermal interface evaporation device for desalination of brackish water. Background Art
[0002] Photothermal composite materials are multifunctional materials that can efficiently absorb solar energy and convert it into thermal energy. They are special performance materials formed by artificially compounding two or more materials with different properties. This characteristic of photothermal composite materials makes them have great potential in solving the global freshwater resource shortage and energy crisis. In recent years, photothermal composite materials have been widely used in seawater desalination, temperature difference power generation, wearable health monitoring and other fields with high efficiency and environmental protection.
[0003] Groundwater resources are an important component of water resource utilization and play an important role in the drinking water source in western my country. However, about one-third of groundwater resources are brackish water that is unsuitable or cannot be directly drunk. For example, in arid areas such as the Northwest and the North China Plain, there has always been a problem of drinking brackish water. In some areas, there is high-fluoride groundwater. In coastal areas, there is a problem of groundwater brackish water caused by seawater infiltration. Especially in the arid and semi-arid areas in northern my country where surface water resources are relatively scarce, groundwater brackish water is sometimes even the only source of water. Therefore, the study and utilization of groundwater brackish water resources plays a very important role in ensuring the domestic water supply of urban and rural residents in my country, supporting the positive development of society, and maintaining ecological balance.
[0004] "Bitter and salty water" is a long-standing popular term that refers to water that tastes bitter and is difficult to drink directly. Long-term drinking often leads to gastrointestinal disorders and low immunity. The total amount of groundwater resources that can be exploited in my country is 352.778 billion cubic meters per year, of which 19.848 billion cubic meters are bitter and salty water resources that can be exploited per year. The areas covered by bitter and salty water account for 16% of the country's land area.
[0005] With the development of my country's economy and society, it is expected that when my country's population reaches its peak in 2030, the most serious water shortages will be in the eastern coastal areas, the western brackish water areas and large and medium-sized inland cities. Therefore, it is of great significance to study and develop practical technologies for utilizing non-traditional water resources (seawater, brackish water) and to introduce new concepts to prepare efficient and stable new brackish water desalination devices. The moderate development of brackish water is an urgent task. It is an industry with high technology content and high added value, and is in a period of urgent development.
[0006] At present, the technical research and development of products in the field of brackish water desalination mainly focuses on distillation, electrodialysis, reverse osmosis, etc. Distillation is the process of heating brackish water to boil and evaporate, and then condensing the steam into fresh water. There are many types of distillation methods, such as multi-effect evaporation, multi-stage flash evaporation, compressed steam distillation, membrane distillation, etc., but its power consumption is large, the operating cost is high; it is easy to corrode and scale. Electrodialysis is a separation technology that uses ion exchange membranes under the action of electric fields to separate anions and cations in salt water, thereby reducing the salt concentration in the fresh water chamber to obtain fresh water. However, the higher the salt content of brackish water, the greater the energy consumption. Therefore, electrodialysis is more suitable for the desalination of low-salinity brackish water. At the same time, this method cannot effectively remove organic matter and bacteria in the water, which limits its application in brackish water desalination projects. Reverse osmosis is the most commonly used method at present, but its equipment has high operating costs, and still has the disadvantages of excessive initial investment costs and low output efficiency due to long-term continuity. It also has certain limitations.
[0007] At present, the brackish water desalination device based on the super-wetting surface interface material has good feasibility, which relies on the reasonable distribution of super-hydrophobic and super-hydrophilic areas on the surface and inside of the substrate to evaporate and condense brackish water droplets under light, and then uses other components to accumulate water. However, most of the typical super-hydrophobic materials on the market obtain excellent water contact angles by introducing special fluoropolymers, and the low surface energy substances used in the preparation process of general super-hydrophobic materials mostly rely on long fluorine or perfluorinated carbon chain compounds containing C8 and above, but such compounds are difficult to degrade in the natural environment and are expensive. With the increasing attention paid to the ecological environment and life and health, more and more long fluorine or perfluorinated compounds are restricted because of their toxicity and bioaccumulation, which are harmful to the ecological environment and human health. At the same time, the existing preparation routes and construction methods have the disadvantages of high raw material costs, excessive reliance on professional instruments and equipment, and lengthy process links, which seriously restrict the practical application of super-wetting surface interface materials for brackish water desalination, and are not conducive to promoting the development of brackish water desalination devices with extreme wetting ability. Therefore, it is necessary to use short fluorine-carbon chain or fluorine-free low surface energy materials with similar functions and lower costs to replace them. Under the development trend of green sustainability, clean production, and efficient and short processes, how to prepare super-wetting products and brackish water desalination devices with wide sources, simple and easy operation, mild parameter conditions, and environmental stimulus response wetting behavior regulation is still a research difficulty that researchers and academic teams are focusing on. It is particularly urgent to endow brackish water desalination and photothermal evaporation capabilities on flexible substrates. Therefore, the use of photothermal composite friction-constructed photothermal interface evaporation devices for brackish water desalination has significant application prospects in the field of brackish water desalination. Summary of the invention
[0008] In view of the defects of the prior art, the present invention, on the one hand, provides a convenient friction construction method for a self-floating photothermal interface evaporation device for desalination of brackish water, which solves the problems of complex preparation process, high energy consumption, high cost, and requirement for expensive large-scale professional equipment of existing photothermal composite materials and photothermal interface evaporation devices.
[0009] In order to achieve the above-mentioned object, the technical solution provided by the present invention is a convenient friction construction method of a self-floating photothermal interface evaporation device for brackish water desalination, which comprises the following steps:
[0010] S100, taking a polyacrylate compound and a higher alkyl alcohol, and completely dissolving the polyacrylate compound and the higher alkyl alcohol in anhydrous ethanol;
[0011] S200, adding nano-scale inorganic materials and making the nano-scale inorganic materials uniformly dispersed in the system;
[0012] S300, adding a branched polyamino compound to fully dissolve it, and after the reaction is completed, a black hyperbranched gel polymer is formed;
[0013] S400, adding a long-chain alkylamine to the tetrahydrofuran system to fully dissolve the long-chain alkylamine to obtain a mixed solution;
[0014] S500, placing the black hyperbranched gel polymer in the mixed solution of step S400, and performing low surface energy modification treatment by immersion at room temperature to obtain a fluorine-free super hydrophobic gel polymer composite material;
[0015] S600, selecting various hydrophilic substrates with rough structures on the surface;
[0016] S700, placing the material obtained in step S500 on the hydrophilic substrate described in step S600 and performing reciprocating friction to complete the rapid construction of a wetting asymmetric self-floating photothermal interface evaporation device.
[0017] Furthermore, the hydrophilic substrate in step S600 is a polyvinyl alcohol sponge treated with formalin.
[0018] Preferably, the thickness of the polyvinyl alcohol sponge is 1.25 cm.
[0019] Preferably, the polyacrylate-based compound in step S100 is dipentaerythritol penta- / hexa-acrylic acid.
[0020] Preferably, the mass ratio of dipentaerythritol penta- / hexa-acrylic acid to anhydrous ethanol is 1:6.838.
[0021] Preferably, in step S100, the higher alkyl alcohol is octadecyl alcohol, and when the polyacrylate-based compound is dipentaerythritol pentyl- / hexyl-acrylic acid, the mass ratio of the higher alkyl alcohol to dipentaerythritol pentyl- / hexyl-acrylic acid is 1:1.
[0022] Preferably, the nanoscale inorganic material in step S200 includes hydroxyapatite and a carbon-based photothermal material; the mass ratio of dipentaerythritol penta- / hexa-acrylic acid: hydroxyapatite: carbon-based photothermal material is 3:5:1.
[0023] Preferably, the branched polyamino compound in S300 is polyethyleneimine terminated with ethylenediamine, and the mass ratio of the branched polyamino compound to dipentaerythritol penta- / hexa-acrylic acid is 3:10. The reaction temperature is controlled to be room temperature, and the reaction time is 12 hours.
[0024] Preferably, when the long-chain alkylamine in step S400 is octadecylamine, the mass ratio of the long-chain alkylamine to tetrahydrofuran is 10:89.
[0025] Preferably, in step S500, the reaction temperature is controlled to be room temperature and the reaction time is 48 hours.
[0026] The present invention uses a multi-acrylate-based compound and a branched amino compound to undergo a Michael addition reaction in an anhydrous ethanol liquid phase doped with nano-scale inorganic biomaterials and photothermal materials, utilizes a catalytic-free spontaneous gelation and curing process at room temperature, and then uses a room temperature immersion modification treatment with a long-chain alkylamine to construct a composite gel polymer material with durable superhydrophobicity in a mild manner; the reaction process is mild and the raw materials are from natural sources.
[0027] The present invention adopts the PVA sponge after acetalization as the substrate, and constructs a Janus photothermal sponge with asymmetric wetting by implementing a simple reciprocating friction composite gel polymer material on the surface of the substrate, so as to realize the desalination application in a specific environmental atmosphere. Compared with the existing super-hydrophobic preparation method femtosecond laser etching method, it has a simple process and low cost. In addition, due to its large wettability difference, the liquid will continuously pass through the hydrophilic part to the hydrophilic-hydrophobic junction, further improving the application efficiency of brackish water desalination under photothermal evaporation conditions. And after the water is completely evaporated, the remaining residue can be extracted with chemical substances, and there is also a certain development prospect in the field of fine chemical development.
[0028] The substrate constructed by the self-floating photothermal interface evaporation device of the present invention can be selected from various hydrophilic substrates with rough surfaces, such as waste textiles, etc. It not only has a desalination function, but can also be applied to different regions, thereby meeting the needs of different users.
[0029] The self-floating photothermal interface evaporation device preparation process and material use of the present invention are non-toxic and non-bioaccumulative, and are prepared under room temperature and non-catalytic conditions. The preparation process is simple, efficient and short-process; therefore, the present invention has good innovation and foresight in terms of gentle product forming pathways and simple construction of new brackish water desalination materials, conforms to the concept of green environmental protection, reduces energy consumption, and reduces replacement costs.
[0030] The present invention is different from the existing brackish water desalination devices, which have high maintenance costs and repair costs. The friction-constructed self-floating photothermal interface evaporation device can restore the desalination capacity to the original state by friction again during use, and can also use the ingenious design of the hydrophilic substrate structure to regulate the evaporation capacity of the photothermal interface evaporation device. At the same time, the polymer prepared by the present invention can be added with color and used as super-hydrophobic chalk. Rubbing it on the surface of other substrates can give it color and show super-hydrophobic properties, which is universal; the asymmetric wettability of the photothermal interface evaporation device can achieve selective separation of oil-water mixtures, and the market can be continuously expanded around this product in subsequent development. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is an optical photograph of a black hyperbranched gel polymer before drying in one embodiment of the present invention;
[0032] Figure 2 The optical photograph and surface static water contact angle of the black hyperbranched gel polymer after drying in one embodiment of the present invention;
[0033] Figure 3 This is an optical photograph of the fluorine-free moisture-resistant gel polymer composite material before drying in one embodiment of the present invention;
[0034] Figure 4 The optical photograph of the fluorine-free moisture-resistant gel polymer composite material after drying and its wetting properties in one embodiment of the present invention;
[0035] Figure 5 It is a schematic diagram of the appearance of the air layer of the fluorine-free moisture-resistant gel polymer composite material under water in one embodiment of the present invention and the completely non-wetting state of the surface when it is lifted to the air environment;
[0036] Figure 6 This is a static anti-humidity state diagram of the fluorine-free anti-humidity gel polymer composite material after being rubbed against the PVA sponge after formalin in one embodiment of the present invention;
[0037] Figure 7 It is a schematic diagram of the wetting performance and dynamic anti-wetting of the fluorine-free anti-wetting gel polymer composite material after being rubbed against the PVA sponge after formalin in one embodiment of the present invention;
[0038] Figure 8It is a schematic diagram of the anti-fouling of the fluorine-free moisture-resistant gel polymer composite material after being rubbed against the PVA sponge after formalin in one embodiment of the present invention;
[0039] Fig. 9 This is a schematic diagram of the directional moisture permeability of water droplets in a PVA sponge after formalization in one embodiment of the present invention;
[0040] Fig.10 A schematic diagram of a photothermal interface evaporation device for brackish water desalination in one embodiment of the present invention;
[0041] Fig.11 The sinking process of the original sponge in water;
[0042] Fig.12 The photothermal interface evaporation device in one embodiment of the present invention is in a floating state when placed in water;
[0043] Fig.13 Demonstrating the self-floating capability of the photothermal interface evaporation device in one embodiment of the present invention;
[0044] Fig.14 The floating stability test process of the photothermal interface evaporation device on the water surface in one embodiment of the present invention is demonstrated;
[0045] Fig.15 A schematic diagram of friction preparation of a photothermal interface evaporation device in one embodiment of the present invention;
[0046] Fig.16 This is a diagram of a brackish water desalination test device for a photothermal interface evaporation device according to an embodiment of the present invention;
[0047] Fig.17 The temperature of pure water surface changes with time under 1 Sun for photothermal interface evaporation devices with different thicknesses;
[0048] Fig.18 The variation of pure water evaporation mass over time under 1 Sun for photothermal interface evaporation devices with different thicknesses;
[0049] Fig.19 The response curve of the surface temperature of the photothermal interface evaporation device under 0.5-2 Sun irradiation in one embodiment of the present invention;
[0050] Fig. 20 This is an infrared thermal imaging image of the photothermal interface evaporation device and the original sponge in one embodiment of the present invention under dry conditions for the first 6 minutes of 1 Sun irradiation;
[0051] Fig.21 The evaporation rate of pure water of the photothermal interface evaporation device under different light intensities in one embodiment of the present invention;
[0052] Fig. 22The evaporation quality of brackish water simulated by the photothermal interface evaporation device in one embodiment of the present invention for 6 hours under 1 Sun;
[0053] Fig.23 The evaporation performance of the photothermal interface evaporation device in one embodiment of the present invention simulates the evaporation performance of brackish water under 1 Sun for 12 consecutive cycles;
[0054] Fig.24 This is an optical photograph of brackish water evaporating under natural sunlight in a photothermal interface evaporation device according to an embodiment of the present invention;
[0055] Fig.25 The outdoor temperature of the photothermal interface evaporation device under natural sunlight from 10:00 to 18:00 (October 11, 2023) and the surface temperature of the photothermal interface evaporation device in one embodiment of the present invention;
[0056] Fig.26 It is the real-time sunlight intensity and hourly evaporation rate of the photothermal interface evaporation device in one embodiment of the present invention. DETAILED DESCRIPTION
[0057] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0058] Example 1
[0059] The present invention provides a convenient friction construction method for a self-floating photothermal interface evaporation device for brackish water desalination, which comprises the following steps:
[0060] Step S100, weighing 1.5 g of dipentaerythritol penta- / hexyl-acrylic acid and adding it to a glass container, then adding 10 ml of anhydrous ethanol to the glass container, shaking to make the dipentaerythritol penta- / hexyl-acrylic acid completely dissolved in the anhydrous ethanol, then adding 1.5 g of octadecyl alcohol, stirring to make the octadecyl alcohol fully dissolved, to obtain a mixed solution; in this embodiment, the higher alkyl alcohol is octadecyl alcohol, in other embodiments, the higher alkyl alcohol can be dodecanol, tetradecanol, hexadecanol, etc., and the super hydrophobic gel polymer composite material obtained by adding octadecyl alcohol in this embodiment has the best anti-moisture effect.
[0061] Step S200, adding 0.5g of carbon nanotubes and 2.5g of nano-hydroxyapatite to the mixed solution of step S100, stirring to make the carbon nanotubes and the nano-hydroxyapatite evenly dispersed in the system; in this embodiment, carbon-based photothermal materials preferably use carbon nanotubes. In other embodiments, in addition to carbon nanotubes, carbon-based photothermal materials can also be selected from graphene, carbon black, carbon dots, amorphous carbon and other materials with photothermal effects.
[0062] Step S300, adding 0.47 g of ethylenediamine-terminated polyethyleneimine to the mixed solution obtained in step S200, dissolving it fully, standing it until the reaction is complete, and drying it to form a uniform black hyperbranched gel polymer;
[0063] Step S400, adding 1.5 g of octadecylamine to 15 ml of tetrahydrofuran (THF) to fully dissolve the octadecylamine to obtain a mixed solution;
[0064] Step S500, placing the hyperbranched gel polymer obtained in step S300 in the mixed solution of step S400, and allowing it to stand for 48 hours of low surface energy modification treatment at room temperature to obtain a fluorine-free moisture-resistant gel polymer composite material;
[0065] Step S600, select the PVA sponge after formal treatment as the hydrophilic substrate; in this embodiment, the hydrophilic substrate with a rough surface structure uses the PVA sponge after formal treatment as the hydrophilic substrate. In other embodiments, the hydrophilic substrate can also be made of wood, knitted cotton, foam sheet, sandpaper, corrugated paper, basswood and other materials. However, in this embodiment, the photothermal evaporation device constructed with "polyvinyl alcohol sponge after formal treatment" as the substrate has a higher pure water evaporation rate, and the evaporation rate for desalination of brackish water is also higher.
[0066] Step S700: Apply the fluorine-free moisture-resistant gel polymer composite material prepared in step S500 to the PVA sponge substrate treated with formalin and cut to a size of 2*2*0.5 cm as described in step S600. Through a simple reciprocating friction technique, it is found that the load reaches a saturated state after 10 frictions. The total load after friction is calculated to obtain a single average friction load of about 8.29 mg·cm -2 , thereby quickly constructing a self-floating photothermal interface evaporation device with wetting asymmetric characteristics.
[0067] Example 2
[0068] The present invention provides a convenient friction construction method for a self-floating photothermal interface evaporation device for brackish water desalination, which comprises the following steps:
[0069] Step S100, weighing 1.5 g of dipentaerythritol penta- / hexyl-acrylic acid and adding it to a glass container, then adding 10 ml of anhydrous ethanol to the glass container, shaking to make the dipentaerythritol penta- / hexyl-acrylic acid completely dissolved in the anhydrous ethanol, then adding 1.5 g of octadecyl alcohol, stirring to make the octadecyl alcohol fully dissolved, to obtain a mixed solution;
[0070] Step S200: adding 0.5 g of carbon nanotubes and 2.5 g of nano-hydroxyapatite to the mixed solution of step S100, and stirring to make the carbon nanotubes and the nano-hydroxyapatite uniformly dispersed in the system.
[0071] Step S300, adding 0.47 g of ethylenediamine-terminated polyethyleneimine to the mixed solution obtained in step S200, dissolving it fully, standing it until the reaction is complete, and drying it to form a uniform black hyperbranched gel polymer;
[0072] Step S400, adding 1.5 g of octadecylamine to 15 ml of tetrahydrofuran (THF) to fully dissolve the octadecylamine to obtain a mixed solution;
[0073] Step S500, placing the hyperbranched gel polymer obtained in step S300 in the mixed solution of step S400, and allowing it to stand for 48 hours of low surface energy modification treatment at room temperature to obtain a fluorine-free moisture-resistant gel polymer composite material;
[0074] Step S600, selecting a PVA sponge after formalization as a hydrophilic substrate;
[0075] Step S700: Apply the fluorine-free moisture-resistant gel polymer composite material prepared in step S500 to the PVA sponge substrate treated with formalin and cut to a size of 2*2*0.75 cm as described in step S600. Through a simple reciprocating friction technique, it was found that the load reached a saturated state after 10 frictions, and the total load after friction was calculated to obtain a single average friction load of about 8.29 mg·cm -2 , thereby quickly constructing a self-floating photothermal interface evaporation device with wetting asymmetric characteristics.
[0076] Example 3
[0077] The present invention provides a convenient friction construction method for a self-floating photothermal interface evaporation device for brackish water desalination, which comprises the following steps:
[0078] Step S100, weighing 1.5 g of dipentaerythritol penta- / hexyl-acrylic acid and adding it to a glass container, then adding 10 ml of anhydrous ethanol to the glass container, shaking to make the dipentaerythritol penta- / hexyl-acrylic acid completely dissolved in the anhydrous ethanol, then adding 1.5 g of octadecyl alcohol, stirring to make the octadecyl alcohol fully dissolved, to obtain a mixed solution;
[0079] Step S200, adding 0.5 g of carbon nanotubes and 2.5 g of nano-hydroxyapatite to the mixed solution of step S100, and stirring to make the carbon nanotubes and the nano-hydroxyapatite uniformly dispersed in the system;
[0080] Step S300, adding 0.47 g of ethylenediamine-terminated polyethyleneimine to the mixed solution obtained in step S200, dissolving it fully, standing it until the reaction is complete, and drying it to form a uniform black hyperbranched gel polymer;
[0081] Step S400, adding 1.5 g of octadecylamine to 15 ml of tetrahydrofuran (THF) to fully dissolve the octadecylamine to obtain a mixed solution;
[0082] Step S500, placing the hyperbranched gel polymer obtained in step S300 in the mixed solution of step S400, and allowing it to stand for 48 hours of low surface energy modification treatment at room temperature to obtain a fluorine-free moisture-resistant gel polymer composite material;
[0083] Step S600, selecting a PVA sponge after formalization as a hydrophilic substrate;
[0084] Step S700: Apply the fluorine-free moisture-resistant gel polymer composite material prepared in step S500 to the PVA sponge substrate treated with formalin and cut to a size of 2*2*1.0 cm as described in step S600. Through a simple reciprocating friction technique, it was found that the load reached a saturated state after 10 frictions, and the total load after friction was calculated to obtain a single average friction load of about 8.29 mg·cm -2 , thereby quickly constructing a self-floating photothermal interface evaporation device with wetting asymmetric characteristics.
[0085] Example 4
[0086] The present invention provides a convenient friction construction method for a self-floating photothermal interface evaporation device for brackish water desalination, which comprises the following steps:
[0087] Step S100, weighing 1.5 g of dipentaerythritol penta- / hexyl-acrylic acid and adding it to a glass container, then adding 10 ml of anhydrous ethanol to the glass container, shaking to make the dipentaerythritol penta- / hexyl-acrylic acid completely dissolved in the anhydrous ethanol, then adding 1.5 g of octadecyl alcohol, stirring to make the octadecyl alcohol fully dissolved, to obtain a mixed solution;
[0088] Step S200, adding 0.5 g of carbon nanotubes and 2.5 g of nano-hydroxyapatite to the mixed solution of step S100, and stirring to make the carbon nanotubes and the nano-hydroxyapatite uniformly dispersed in the system;
[0089] Step S300, adding 0.47 g of ethylenediamine-terminated polyethyleneimine to the mixed solution obtained in step S200, dissolving it fully, standing it until the reaction is complete, and drying it to form a uniform black hyperbranched gel polymer;
[0090] Step S400: add 1.5 g of octadecylamine into 15 ml of tetrahydrofuran (THF) to fully dissolve the octadecylamine to obtain a mixed solution.
[0091] Step S500, placing the hyperbranched gel polymer obtained in step S300 in the mixed solution of step S400, and allowing it to stand for 48 hours of low surface energy modification treatment at room temperature to obtain a fluorine-free moisture-resistant gel polymer composite material;
[0092] Step S600, selecting a PVA sponge after formalization as a hydrophilic substrate;
[0093] Step S700: Apply the fluorine-free moisture-resistant gel polymer composite material prepared in step S500 to the PVA sponge substrate treated with formalin and cut to a size of 2*2*1.25 cm as described in step S600. Through a simple reciprocating friction technique, it was found that the load reached a saturated state after 10 frictions, and the total load after friction was calculated to obtain a single average friction load of about 8.29 mg·cm -2 , thereby quickly constructing a self-floating photothermal interface evaporation device with wetting asymmetric characteristics.
[0094] Example 5
[0095] The present invention provides a convenient friction construction method for a self-floating photothermal interface evaporation device for brackish water desalination, which comprises the following steps:
[0096] Weigh 1.5 g of dipentaerythritol penta- / hexyl-acrylic acid and add it to a glass container, then add 10 ml of anhydrous ethanol to the glass container, shake to make the dipentaerythritol penta- / hexyl-acrylic acid completely dissolved in the anhydrous ethanol, then add 1.5 g of octadecyl alcohol and stir to make the octadecyl alcohol fully dissolved to obtain a mixed solution;
[0097] Step S200, adding 0.5 g of carbon nanotubes and 2.5 g of nano-hydroxyapatite to the mixed solution of step S100, and stirring to make the carbon nanotubes and the nano-hydroxyapatite uniformly dispersed in the system;
[0098] Step S300, adding 0.47 g of ethylenediamine-terminated polyethyleneimine to the mixed solution obtained in step S200, dissolving it fully, standing it until the reaction is complete, and drying it to form a uniform black hyperbranched gel polymer;
[0099] Step S400: add 1.5 g of octadecylamine into 15 ml of tetrahydrofuran (THF) to fully dissolve the octadecylamine to obtain a mixed solution.
[0100] Step S500, placing the hyperbranched gel polymer obtained in step S300 in the mixed solution of step S400, and allowing it to stand for 48 hours of low surface energy modification treatment at room temperature to obtain a fluorine-free moisture-resistant gel polymer composite material;
[0101] Step S600, selecting a PVA sponge after formalization as a hydrophilic substrate;
[0102] Step S700: Apply the fluorine-free moisture-resistant gel polymer composite material prepared in step S500 to the PVA sponge substrate treated with formalin and cut to a size of 2*2*1.5 cm as described in step S600. Through a simple reciprocating friction technique, it was found that the load reached a saturated state after 10 frictions, and the total load after friction was calculated to obtain a single average friction load of about 8.29 mg·cm -2 , thereby quickly constructing a self-floating photothermal interface evaporation device with wetting asymmetric characteristics.
[0103] In the above embodiment, since nano-inorganic materials are added in step S200, and the nano-inorganic materials include hydroxyapatite and carbon nanotubes, higher alkyl alcohol is added in step S100, that is, the higher alkyl alcohol and the nano-inorganic materials are added in two steps rather than in the same step, which can increase the contact area between the anhydrous ethanol solution containing the polyacrylate-based compound dissolved in step S100 and the higher alkyl alcohol to a certain extent, and is beneficial to the dissolution of the higher alkyl alcohol.
[0104] In Examples 1 to 5, a PVA sponge after condensation is selected as a hydrophilic substrate. Without the aid of an adhesive, a Janus photothermal sponge with asymmetric wetting is constructed by simply performing a simple reciprocating friction on the surface of the sponge substrate, thereby realizing the photothermal evaporation application of brackish water in a specific environmental atmosphere. In addition, due to the super-hydrophilicity of the bottom substrate sponge, brackish water can be continuously transported to the junction with the photothermal layer, thereby accelerating the evaporation progress and further improving the efficiency of brackish water desalination applications under photothermal evaporation conditions. In step S600, a PVA sponge after condensation is used as a substrate, and a composite gel polymer material with simple reciprocating friction is performed on the surface of the substrate to construct a photothermal interface evaporation device with asymmetric wetting.
[0105] The overall preparation process of the photothermal composite material does not involve any chemical-induced polymerization, and an environmentally friendly composite gel polymer material with a significant "lotus leaf effect" superhydrophobic property is constructed without the need for an external driver. In addition, the photothermal interface evaporation device is based on the asymmetry of the wettability of the superhydrophobic surface of the material coating and the superhydrophilic end of the sponge itself, resulting in a difference in wettability, which allows the sponge to continuously absorb water based on its own superhydrophilicity to fill the sponge with water, while the coating has excellent hydrophobicity, and water can be continuously absorbed into the coating for evaporation without being wetted. Water is continuously transported from the superhydrophilic part to the junction with the superhydrophobic surface with the photothermal effect, which improves the evaporation efficiency and can repair the photothermal capacity wear caused by previous use by re-rubbing.
[0106] The photothermal interface evaporation device preparation process and materials used in the above embodiments are non-toxic, non-bioaccumulative, and are prepared at room temperature without catalysis. The preparation process is simple, efficient, and short.
[0107] Table 1 is a summary table of the mass of materials added in Examples 1 to 5;
[0108]
[0109] It should be noted that the steps and operations of Examples 1 to 5 are basically the same, except that the prepared fluorine-free anti-wetting gel polymer composite material is reciprocated and rubbed on sponges of different thicknesses to construct a self-floating photothermal interface evaporation device with asymmetric wetting properties. Photothermal performance tests, floating performance tests, evaporation performance tests, outdoor tests, etc. were conducted on Examples 1 to 5, respectively. The photothermal interface evaporation device showed the best evaporation efficiency when the sponge thickness was 1.25 cm. The test process of the product of Example 4 is described below as an example.
[0110] 1. Determination of the wetting properties of fluorine-free anti-wetting gel polymer composites, see Figure 1-Figure 10 ;
[0111] The specific determination methods of wetting characteristics include:
[0112] H100, static water contact angle measurement: 5 μL of deionized water was added to five different areas of the sample, the contact angle of each water drop was measured using the instrument, and then the average of these measured values was taken to obtain the static water contact angle data.
[0113] H200, Rolling angle measurement: By adjusting the angle on the tilting stage, when 10 μL of deionized water is added to five different positions of the sample and it is allowed to roll, this specific angle is recorded and fixed. This angle is the rolling angle of the sample.
[0114] H300, static moisture resistance observation: add water droplets to the sample surface and observe the static state of the water droplets to evaluate the moisture resistance of the sample.
[0115] H400, moisture resistance test under photothermal interface evaporation: Build a photothermal interface evaporation device on the inclined sample surface, and drop water on it to observe whether the water droplets can roll off automatically. At the same time, check whether there are any water droplets remaining on the sample surface to evaluate the moisture resistance of the sample.
[0116] in, Figure 1 This is an image of the gel polymer before it dries. Figure 2 This is the optical image and static water contact angle of the gel polymer after drying, which is 0°, indicating superhydrophilicity. Figure 3 , Figure 4 They are the appearance morphology of the fluorine-free anti-humidity gel polymer composite material prepared after immersion modification at room temperature before and after drying, as well as the contact angle and rolling angle after drying. The contact angle is 157.8° and the rolling angle is 0.5°, indicating super hydrophobicity.
[0117] like Figure 5 As shown, after the impurities in the prepared fluorine-free moisture-resistant gel polymer composite material are gently scraped off and completely immersed in deionized water, an obvious air layer is found on the surface. When it is brought to an air atmosphere, the polymer surface is dry and not wet at all, and still maintains good moisture resistance.
[0118] The substrate with a rough surface structure in the present invention is a PVA sponge after formalization, see Figure 6-Figure 10 , showing that the composite material was uniformly rubbed on the surface of a PVA sponge after formalin, and the static water contact angle on the sponge was measured to be 156.28°, and the rolling angle was 0.5°. The dye droplets did not show wetting behavior on the friction-structured photothermal interface evaporation device, and the device proved the long-lasting stability of its superhydrophobic properties in practical applications. This shows that the superhydrophobicity and stability of the product are excellent. It should be noted that the hydrophilic substrate with a rough structure on the surface and capable of attaching anti-wetting gel polymer composite particles can achieve surface superhydrophobicity through simple reciprocating friction, thereby constructing a self-floating photothermal interface evaporation device for water purification processes.
[0119] 2. Test the floating performance of the photothermal interface evaporation device, see Figure 11-Figure 14
[0120] The original sponge substrate and the friction-structured photothermal interface evaporation device were placed in water at the same time to compare their floating abilities. Use tweezers to press the photothermal interface evaporation device to the bottom of the beaker to observe whether it can float up, and record the time it takes to float on the water surface to test its floating ability. Put the photothermal interface evaporation device in water, record the date after the superhydrophilic part absorbs water and sinks naturally, observe how long it can continue to float on the water surface, and evaluate its self-floating durability.
[0121] Depend on Fig.11 It can be seen that after the original sponge continuously absorbed water and reached saturation, it completely sank to the bottom of the cup in 40 seconds; Fig.12 and Fig.13 The unrubbed super-hydrophilic part on the lower side of the photothermal interface evaporation device quickly absorbed water and became wetted. It did not sink after saturation and continued to float on the surface of the liquid. When tweezers were used to apply pressure to press the photothermal interface evaporation device to the bottom of the beaker, it was observed that there was an obvious air layer on the coating surface. After the external force was removed, the photothermal interface evaporation device was able to quickly float up within two seconds and stably float on the water surface, showing good floating performance.
[0122] Fig.14 To further explore the self-floating durability of the photothermal interface evaporation device, it was placed in deionized water and the time it could maintain the floating state was recorded. It was found that it could float stably on the surface for 7 days and tilted on the 8th day, indicating that the photothermal interface evaporation device has stable and excellent superhydrophobic properties and self-floating properties.
[0123] In the floating state, the coating surface of the photothermal interface evaporation device does not have any water infiltration, is not wetted, and will not be submerged by water, creating a very good evaporation interface for photothermal desalination. During the evaporation process, only a small amount of water is heated and evaporated, avoiding energy loss caused by sunlight irradiating too large an area of water, thereby improving the utilization efficiency of solar energy.
[0124] 3. Construction of photothermal interface evaporation device, see Figure 15-16
[0125] The PVA sponge treated with formalin was cut into a sponge block with a front surface of 2x2 cm and a height of 1.25 cm. The prepared fluorine-free anti-wetting gel polymer was rubbed back and forth on the front surface to construct a 2×2 cm photothermal superhydrophobic coating that completely covered one surface of the sponge, and the loading amount of the coating particles on the surface of the sponge substrate after friction reached a specified value, and a photothermal evaporation device was prepared, such as Fig.15 shown.
[0126] from Fig.16It can be seen that the photothermal interface device consists of three parts: a simulated light source, an evaporation device, and an electronic balance. Among them, a xenon lamp is used to simulate sunlight, and the irradiation intensity is tested with the help of an optical power meter. In the experiment of the evaporation process of brackish water, an electronic balance is used for continuous weighing to accurately determine its mass change. By analyzing the data, the evaporation rate of the product can be calculated. The evaporation device needs to add a thermal insulation layer to avoid excessive contact between the photothermal evaporation interface and the water body, so as to prevent heat conduction to the surrounding area and cause losses as much as possible. In order to simulate the actual application scenario, no thermal insulation layer was added in the following tests and simulations.
[0127] 4. Evaporation performance of the photothermal interface evaporation device for simulated brackish water, see Figure 17-Figure 26
[0128] The schematic diagram of the photothermal interface evaporation device clearly shows the water surface coverage behavior of the brackish water desalination test process without the insulation layer. The photothermal interface evaporation device with a thickness of 1.25 cm was placed under the condition of 1 sun intensity for testing. The changes of pure water quality and temperature over time are shown in the figure. Fig.17 , 18 As shown in Figure 2, the evaporation rate of the super-hydrophilic part with a thickness of 1.25 cm is as high as 2.875 kg·m -2 ·h -1 , is pure water (0.5143kg·m -2 ·h -1 ) is 5.5 times.
[0129] The infrared thermal imager test found that the surface temperature of the 1.25cm thick photothermal interface evaporation device during water evaporation was 38.5℃, which was much higher than the 31.9℃ of 0.5cm and 31.3℃ of 1.5cm. This phenomenon may be due to the small distance between the photothermal coating and the water surface, resulting in ineffective heat transfer, or the substrate absorbed too much water, thereby reducing the temperature of the evaporation interface.
[0130] like Fig.19 , 20As shown in the figure, when the temperature response test of the photothermal interface evaporation device was carried out, the temperature of the device surface showed a significant upward trend with the increase of solar irradiation intensity. As the irradiation time of the xenon lamp increased, the temperature of the surface of the photothermal interface evaporation device continued to rise; after the xenon lamp light source was turned off, the temperature began to drop, and its surface temperature changed rapidly with the start and end of irradiation. In particular, under the irradiation intensity of 1 sun, the surface temperature of the device quickly rose to 63.6℃ in the first 120 seconds, and stabilized in the following 300 seconds, reaching an equilibrium temperature of about 69.6℃. This phenomenon shows that the photothermal interface evaporation device can efficiently convert the absorbed light energy into heat energy, thereby achieving rapid temperature rise, which is crucial to improving the evaporation rate. In addition, compared with the untreated PVA sponge, the photothermal interface evaporation device showed a significant advantage in photothermal conversion performance. During the 300-second test time, the surface temperature of the untreated PVA sponge only reached 54.2℃, which was much lower than the surface temperature of the photothermal interface evaporation device, further confirming the superiority of the photothermal interface evaporation device in photothermal conversion efficiency. This efficient photothermal conversion capability provides a solid foundation for increasing the evaporation rate and achieving efficient water purification.
[0131] The intensity of solar radiation also has a great influence on the evaporation rate of the photothermal interface evaporation device. Fig.21 The photothermal interface evaporation device was used to test the evaporation of simulated brackish water under different light intensities. As the light intensity increases, the evaporation rate of the photothermal interface evaporation device also increases proportionally, indicating that with the increase in solar energy input, the accumulation of freshwater resources will also increase accordingly. Under different solar light intensities, the evaporation performance of the photothermal interface evaporation device shows significant differences. Specifically, under 0.5, 1, 1.5, and 2 sun irradiation intensities, the evaporation rate of the device can reach 1.625kg·m -2 ·h -1 , 2.275kg·m -2 ·h -1 , 2.8kg·m -2 ·h -1 、3.475kg·m -2 ·h -1 . This phenomenon reflects the direct impact of solar irradiance on the evaporation process, in which the evaporation rate is proportional to the intensity of solar irradiation. The photothermal interface evaporation device can still maintain a high evaporation efficiency under low irradiation conditions, which has important practical significance for solar-driven water purification technology. It means that even when the solar irradiation is not particularly strong, the photothermal interface evaporation device can work effectively, thus providing the possibility of a stable supply of fresh water resources.
[0132] Fig. 22 and Fig.23In order to evaluate the continuous evaporation capacity of the photothermal interface evaporation device, a 6-hour continuous brackish water evaporation experiment and 12 cycles of irradiation of the sample were carried out under the condition of 1 sun intensity. There was no significant decrease in the evaporation rate of both, so the photothermal interface evaporation device has a stable evaporation capacity and can be widely used in the field of brackish water desalination.
[0133] like Fig.24 In order to evaluate the actual application of the photothermal interface evaporation device under natural lighting conditions, the photothermal interface evaporation device was placed in brackish water and placed in a cool place. The quality before the test was recorded, and the initial surface temperature of the photothermal interface evaporation device was measured using an infrared thermal imager. It was placed on an unobstructed roof that could be directly exposed to the sun, and an optical power meter was placed next to it. The changes in light intensity, the surface temperature of the photothermal interface evaporation device, and the evaporation rate during the outdoor test were recorded every 30 minutes. Fig.25 , 26 The display is displayed when the intensity is less than 0.6 sun (600W·m -2 ) under the irradiation of the photothermal interface evaporation device, the surface temperature of the device continued to rise from 13.9°C to 45.9°C. The test lasted from 10:00 am to 18:00 pm. During the test, the outdoor sunlight intensity ranged from 0.291 to 0.591 kW·m -2 The average solar radiation intensity is about 0.445kW·m -2 The evaporation rate of the product from 14:00 to 15:00 was as high as 1.84 kg·m -2 ·h -1 The test results show that this low-cost, easy-to-prepare photothermal interface evaporation device has great potential in the practical application of brackish water desalination.
[0134] The reagents used in this example were all analytically pure.
[0135] In addition, it should be understood that the above-described embodiments are only used to explain the present invention in detail, but the present invention is not limited to the above-mentioned detailed methods. For those skilled in the art, within the spirit and principle of the present invention, any improvement of the present invention, equivalent replacement of each raw material of the product of the present invention, selection of specific methods, etc., should all be included in the protection scope and disclosure scope of the present invention.
Claims
1. A convenient friction construction method for a self-floating photothermal interface evaporation device for brackish water desalination, characterized in that: The following steps are involved: S100, taking a polyacrylate compound and a higher alkyl alcohol, and completely dissolving the polyacrylate compound and the higher alkyl alcohol in anhydrous ethanol; S200, adding nano-scale inorganic materials and making the nano-scale inorganic materials uniformly dispersed in the system; S300, adding a branched polyamino compound to fully dissolve it, and after the reaction is completed, a black hyperbranched gel polymer is formed; S400, adding a long-chain alkylamine to the tetrahydrofuran system to fully dissolve the long-chain alkylamine to obtain a mixed solution; S500, placing the black hyperbranched gel polymer in the mixed solution of step S400, and performing low surface energy modification treatment by immersion at room temperature to obtain a fluorine-free super hydrophobic gel polymer composite material; S600, selecting various hydrophilic substrates with rough structures on the surface; S700, placing the material obtained in step S500 on the hydrophilic substrate described in step S600 and performing reciprocating friction to complete the rapid construction of a wetting asymmetric self-floating photothermal interface evaporation device.
2. The convenient friction construction method of the self-floating photothermal interface evaporation device for brackish water desalination according to claim 1 is characterized in that: The hydrophilic substrate in step S600 is a polyvinyl alcohol sponge treated with formalin.
3. The convenient friction construction method of the self-floating photothermal interface evaporation device for brackish water desalination according to claim 2 is characterized in that: The thickness of the polyvinyl alcohol sponge is 1.25 cm.
4. The convenient friction construction method of the self-floating photothermal interface evaporation device for brackish water desalination according to claim 1 is characterized in that: The polyacrylate-based compound in step S100 is dipentaerythritol penta- / hexa-acrylic acid.
5. The convenient friction construction method of the self-floating photothermal interface evaporation device for brackish water desalination according to claim 4 is characterized in that: The mass ratio of dipentaerythritol penta- / hexa-acrylic acid to anhydrous ethanol is 1:6.
838.
6. The convenient friction construction method of the self-floating photothermal interface evaporation device for brackish water desalination according to claim 1 is characterized in that: In step S100, the higher alkyl alcohol is octadecyl alcohol, and when the polyacrylate-based compound is dipentaerythritol pentyl- / hexyl-acrylic acid, the mass ratio of the higher alkyl alcohol to dipentaerythritol pentyl- / hexyl-acrylic acid is 1:
1.
7. The convenient friction construction method of the self-floating photothermal interface evaporation device for brackish water desalination according to claim 6 is characterized in that: The nanoscale inorganic material in step S200 includes hydroxyapatite and a carbon-based photothermal material; the mass ratio of dipentaerythritol penta- / hexa-acrylic acid: hydroxyapatite: carbon-based photothermal material is 3:5:
1.
8. The convenient friction construction method of the self-floating photothermal interface evaporation device for brackish water desalination according to claim 3 is characterized in that: The branched polyamino compound in S300 is polyethyleneimine terminated with ethylenediamine, and the mass ratio of the branched polyamino compound to dipentaerythritol penta- / hexyl-acrylic acid is 3:
10. The reaction temperature is controlled to be room temperature, and the reaction time is 12 hours.
9. The convenient friction construction method of a self-floating photothermal interface evaporation device for brackish water desalination according to any one of claims 1 to 8, characterized in that: When the long-chain alkylamine in step S400 is octadecylamine, the mass ratio of the long-chain alkylamine to tetrahydrofuran is 10:
89.
10. The convenient friction construction method of a self-floating photothermal interface evaporation device for brackish water desalination according to any one of claims 1 to 8, characterized in that: In step S500, the reaction temperature is controlled to be room temperature and the reaction time is 48 hours.